Project management simplified a step-by-step process - Karten, Barbara, 1948- (Industrial innovation series, 2016)
Are projects a problem for you? Do your projects cost too much, take too long, or are just not quite right? If so, Project Management Simplified: A Step-by-Step Process is the book for you. It applies well-defined processes for managing projects to managing change in our lives. It describes an approach modeled on a process used successfully in businesses, not-for-profit organizations, schools, and other organizations.